2007
DOI: 10.1080/08958370600985834
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Manganese Concentration and MRI T1 Relaxation Time During 180 Days of Stainless Steel Welding-Fume Exposure in Cynomolgus Monkeys

Abstract: Welders are at risk of being exposed to high concentrations of welding fumes and developing pneumoconiosis or other welding-fume exposure-related diseases. Among such diseases, manganism resulting from welding-fume exposure remains a controversial issue, as although the movement of manganese into specific brain regions has been established, the similar movement of manganese presented with other metals, such as welding fumes, has not been clearly demonstrated as being similar to that of manganese alone. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Slight increases in the manganese concentration were also found in the substantia nigra and basal ganglia (Yu et al, 2003a). In contrast, the same study conducted on non-human primates showed different results from a rodent study, where prolonged inhalation of welding fumes was found to induce a high MRI T1 signal intensity in the basal ganglia with an elevation of the blood manganese level (Sung et al, 2007). Accordingly, to identify the relationship between the manganese concentration in the brain and a high MRI signal intensity in the corresponding brain region, the present study exposed nonhuman primate cynomolgus monkeys to stainless steel welding fumes, while monitoring the change in the MRI signal intensity and examining the distribution of Mn in the brain regions.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Slight increases in the manganese concentration were also found in the substantia nigra and basal ganglia (Yu et al, 2003a). In contrast, the same study conducted on non-human primates showed different results from a rodent study, where prolonged inhalation of welding fumes was found to induce a high MRI T1 signal intensity in the basal ganglia with an elevation of the blood manganese level (Sung et al, 2007). Accordingly, to identify the relationship between the manganese concentration in the brain and a high MRI signal intensity in the corresponding brain region, the present study exposed nonhuman primate cynomolgus monkeys to stainless steel welding fumes, while monitoring the change in the MRI signal intensity and examining the distribution of Mn in the brain regions.…”
mentioning
confidence: 51%
“…When the robotic arm approached the base stainless-steel plate (SUS 304, 2.5 cm thick) in a zig-zag motion, an arc was produced and the rod was consumed, generating welding fumes. The fumes were then moved into exposure chambers (whole-body type, each 1.5 m 3 , Dusturbo, Seoul) that were rectangular in shape and made of metal with a Plexiglas window (Sung et al, 2007). Each chamber was able to accommodate 2 monkey cages and the total volume occupied by the two monkeys in a chamber was estimated as 1.3%.…”
Section: Materials and Methods Generation Of Manual Metal Arc Stainlementioning
confidence: 99%
See 2 more Smart Citations
“…However, experimental studies on laboratory animals have reported similar results, but studies in human societies have reported conflicting results [23][24] . The use of manganese concentrations in the blood has been studied as a biomarker of exposure to manganese among welders, metal workers, miners and workers making dry batteries [25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Manganese Concentrations In Body Fluids As a Biomarker Of Exmentioning
confidence: 99%